2018
DOI: 10.1128/iai.00724-17
|View full text |Cite
|
Sign up to set email alerts
|

Development of Subunit Vaccines That Provide High-Level Protection and Sterilizing Immunity against Acute Inhalational Melioidosis

Abstract: Burkholderia pseudomallei, the etiologic agent of melioidosis, causes severe disease in humans and animals. Diagnosis and treatment of melioidosis can be challenging, and no licensed vaccines currently exist. Several studies have shown that this pathogen expresses a variety of structurally conserved protective antigens that include cell surface polysaccharides and cell-associated and cell-secreted proteins. Based on those findings, such antigens have become important components of the subunit vaccine candidate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
91
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(102 citation statements)
references
References 60 publications
2
91
2
Order By: Relevance
“…The difference in protective efficacy seen between the Crm197-CPS conjugates used here and the ones used by Burtnick et al [14] could be a result of several experimental differences. Firstly, the different animal models utilised by each lab.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The difference in protective efficacy seen between the Crm197-CPS conjugates used here and the ones used by Burtnick et al [14] could be a result of several experimental differences. Firstly, the different animal models utilised by each lab.…”
Section: Discussionmentioning
confidence: 69%
“…It has been shown that mice vaccinated with conjugates utilising bovine serum albumin as a carrier for CPS or TetHc as a carrier for synthetically-synthesised CPS are significantly protected against non-inhalational B. pseudomallei challenge compared to controls, but sterilising immunity was not achieved in every animal [10, 11]. Recently, one of the most commonly used carrier proteins in licensed conjugate vaccines, Crm197 [12, 13], has been shown to protect mice against an inhalational challenge of B. pseudomallei and achieve high levels of sterilising immunity when conjugated to CPS [14]. This result and the obvious cost and safety advantages of Crm197 justify its use in melioidosis vaccine research but alternative carrier proteins should be sought due to concerns that prior exposure to a carrier can reduce carbohydrate-specific immune responses in other same-carrier-based conjugate vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…Immunization of C57BL/6 mice with CPS-CRM197 produced high-titre immunoglobulin (IgG) and opsonizing antibody responses against the CPS component. When mice were vaccinated with a combination of CPS-CRM197 and recombinant Hcp1, 100% of the mice survived a lethal inhalational challenge with B. pseudomallei [46]. In another study, intraperitoneal immunization with chemically synthesized CPS conjugated to tetanus toxoid promoted IgM and IgG serum antibodies.…”
Section: Multi-component Vaccinesmentioning
confidence: 97%
“…The polysaccharide is a homopolymer of unbranched 1 → 3 linked 2-O-acetyl-6-deoxy-β-D-mannoheptopyranose and is a major virulence determinant in B. pseudomallei . When mice were vaccinated with a combination of CPS-CRM197 and recombinant Hcp1, 100% of the mice survived a lethal inhalational challenge with B. pseudomallei [46]. While CPS purified from B. pseudomallei induces protective immunity against melioidosis in mice, the immune response and protection conferred by CPS, a T-independent antigen, is improved by conjugation to a carrier protein that promotes T cell help [45].…”
Section: Multi-component Vaccinesmentioning
confidence: 99%
“…To this effect, a subunit vaccine has been developed which utilizes purified 6-deoxyheptan CPS from B. pseudomallei linked to recombinant CRM197 diphtheria toxin mutant, together with purified recombinant B. pseudomallei Hcp1 (T6SS-1 effector) and TssM (a deubiquitinase) proteins. 138 Immunization of C57BL/6 mice with CPS-CRM197 results in high-titer immunoglobulin G (IgG) and opsonizing antibody responses, whereas Hcp1 and TssM produce high-titer IgG and robust gamma interferon-secreting T cell responses. 138 A mouse model of this vaccine combination found 100% of mice survived lethal inhalational challenge, with up to 70% showing a sterilizing immune response.…”
Section: Vaccinesmentioning
confidence: 99%